Ancient machines : from wedges to waterwheels - Woods Michael 1946; Woods Mary B 1946 (Minneapolis : Runestone Press, 2000)
Discusses the invention of six simple machines in various ancient civilizations from the Stone Age to the fall of the Roman Empire.
Includes bibliographical references (p. 85) and index.
Keywords: Simple machines -- Juvenile literature; Machinery -- History -- Juvenile literature; Simple machines; Machinery -- History